The Blood of the Colony wine and the rise and fall of French Algeria - White, Owen (Harvard University Press, 2021)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Note on Place Names -- Note on Metric Conversion -- Introduction: The Empire of Wine in Algeria -- Rise and Fall -- People of the Vine -- Wine and the Economic Life of Algeria -- When Is a Colony Not a Colony? -- 1. Roots: Antiquity to 1870 -- The Wine Frontier -- Complementary Colonization -- Settlement and the Wine Question -- Searching for the Wealth of a Colony -- 2. Phylloxera and the Making of the Algerian Vineyard: 1870 to 1907 -- Phylloxera and the "Seduction" of the Colonist -- The Insurgent: Phylloxera in Algeria -- Masters of the Land? -- The Perils of the Market and the Honor of Algerian Wine -- Getting Caught Up with Capital -- 3. Companies and Cooperatives, Work and Wealth: 1907 to 1930 -- Phylloxera, War, and Reconstitution -- War and the Horizon of Capital -- The Cooperative Movement -- Working in the Vines -- Working for the Vines -- Wealth and Influence -- 4. Algeria and the Midi: The 1930s (I) -- Competition versus Complementarity -- Plantation Fever -- Fixing Limits -- Backfire and Backlash -- Allies and Antagonists -- The Tide Crests -- 5. Labor Questions: The 1930s (II) -- Toward "Welfare Viticulture"? -- "Machines of Famine": The First Wine Tankers -- Politicizing the Agricultural Worker -- Violence in the Vines -- Mouths to Feed -- 6. Wine in the Wars: 1940 to 1962 -- Vichy Algeria -- "Liberated" Algeria -- The Other Entre-Deux-Guerres -- The Logic of Descartes -- The Front Lines -- The Hollowing -- The Future and the End -- 7. Pulling Up Roots: Since 1962 -- Self-Management -- Breaking Dependence? -- Wine Repatriated -- Corsica, a New Algeria? -- Algerian Wine at the Margins -- Epilogue: The Geometry of Colonization -- Abbreviations -- Notes -- Acknowledgments -- Index.